O impacto da violência familiar no processo de desenvolvimento de crianças e adolescentes - Gonçalves, Elisabete Alerico (2009)
To deal with family violence against children and adolescents is necessary to know a little more about the subject. Therefore, it is essential to know its conceptual structure, ie, the types of violence and its causes and consequences. In the course of this work also will discuss topics on the complicity between the aggressor and the victim and what it takes to maintain relations of trust and silence. The theme will be presented also look forward to education, where the relationship the school and community goes through a critical analysis, emphasizing the role of the educational institution and the importance of educational proposals. This view is crucial, since it is necessary to know how children and adolescents, victims of family violence are being assisted by the Brazilian education, and education is a key aspect to their development process. Continuing on the subject, still present the legal aspects of family violence on children and adolescents - the placement of the Child and Adolescent and prosecutors towards victims, procedures and measurements performed to solve the problem. Finally, it is a collection of facts presented throughout the dissertation with some proposals to contribute in some way to mitigate the impact of domestic violence in the development of child and adolescent victims of neglect, disrespect and abandonment.